REALISE: Enabling full-chain CCUS for refineries through cluster-based strategies ... - Kim, Inna; Vevelstad, Solrun Johanne; Monteiro, Juliana; Padraig Fleming; Dunphy, Niall (Zenodo, 2021)
Refineries play a major role in our modern lifestyles, creating an almost infinite range of everyday products. Alongside other industries, they face the challenge to decarbonise as part of Europe’s wider efforts to meet climate targets by 2030. This webinar introduced the REALISE CCUS project, an international partnership of industry and scientists working to support the delivery of carbon capture, utilisation and storage (CCUS) technology for the refinery sector. Our research, funded by the European Union's Horizon 2020 programme, focuses on the full CCUS chain – from CO 2 capture, transport and geological CO 2 storage to CO 2 reuse – for clusters which include refineries and other industries. Specifically, we aim to demonstrate CCUS technology, enable sizeable cost-reductions, undertake public engagement and assess financial, political and regulatory barriers. Programme: Welcome & intro – Inna Kim, SINTEF (5 mins) Optimising and validating technologies for refineries (WP1) – Solrun Vevelstad, SINTEF ...